Dengue Shock Syndrome (DSS) complicated by severe hyponatremia and seizure in a pediatric patient: a rare case report - Triola Fitria; Erli Meichory Viorika (Medical Faculty of Brawijaya University, Indonesia, 2025)
Background: Dengue Shock Syndrome (DSS) represents the most severe form of dengue virus infection, driven by massive plasma leakage and profound hemodynamic instability. Severe hyponatremia in this context is uncommon and may precipitate neurological manifestations, including seizure, compounding disease complexity and mortality risk. This study aims to describe the clinical course, management, and outcome of a pediatric DSS case complicated by severe symptomatic hyponatremia and seizure. Case Presentation: We report the case of an 8-year-11-month-old boy presenting with fever, abdominal pain, diarrhea, and a generalized tonic–clonic seizure at home. Laboratory findings confirmed secondary dengue infection, hemoconcentration, thrombocytopenia, and severe hyponatremia (Na⁺ 100–122 mEq/L). The patient developed DSS with large-volume ascites and bilateral pleural effusions during the critical phase. Management included fluid resuscitation per WHO protocol, hypertonic saline correction of sodium, albumin infusion, and close hemodynamic and neurological monitoring. Seizure activity resolved with gradual sodium normalization. Conservative management of effusions avoided invasive intervention. The patient was discharged in stable condition on day six with no recurrent neurological events. This case illustrates the diagnostic and therapeutic challenges of managing DSS complicated by severe hyponatremia and seizure. Management requires balancing volume restoration with prevention of sodium dilution and fluid overload, alongside multidisciplinary coordination. Conclusion: Severe hyponatremia with seizure in DSS is rare but life-threatening. Early electrolyte evaluation in dengue patients with neurological symptoms is essential, and individualized management can optimize survival.